Particular activation phenotype of T cells expressing HLA-DR but not CD38 in GALT from HIV-controllers is associated with immune regulation and delayed progression to AIDS (2016)
The spontaneous control of HIV replication in HIV-controllers underlines the importance of these subjects for exploring factors related to delayed progression. Several studies have revealed fewer immune alterations and effector mechanisms related to viral control, mainly in peripheral blood, in these individuals compared to normal progressors. However, immune characterization of gut-associated lymphoid tissue (GALT), the major target of infection, has not been thoroughly explored in these subjects. We evaluated the following parameters in GALT samples from 11 HIV-controllers and 15 HIV-progressors: (i) frequency and activation phenotype of T cells; (ii) expression of transcription factors associated with immune response profiles; and (iii) frequency of apoptotic cells. Interestingly, HIV-controllers exhibited a particular activation phenotype, with predominance of T cells expressing HLA-DR but not CD38 in GALT. This phenotype, previously associated with better control of infection, was correlated with low viral load and higher CD4? T cell count. Furthermore, a positive correlation of this activation phenotype with higher expression of Foxp3 and RORcT transcription factors suggested a key role for Treg and Th17 cells in the control of the immune activation and in the maintenance of gut mucosal integrity. Although we evaluated apoptosis by measuring expression of cleaved caspase-3 in GALT, we did not find differences between HIV-controllers and HIV-progressors. Taken together, our findings suggest that predominance of HLA-DR+ T cells, along with lower immune activation and higher expression of transcription factors required for the development of Treg and Th17 cells, is associated with better viral control and delayed progression to AIDS.